Poetyka kognitywna dwie dekady później. Rozważania wokół drugiego wydania Cognitive Poetics Petera Stockwella (2020) - Kędra-Kardela, Anna; Kowalczyk, Andrzej Sławomir (Przestrzenie Teorii, 2021)
The article discusses cognitive poetics as an important theoretical framework in contemporary literary studies, in the context of the publication of the second, revised edition of Peter Stockwell’s Cognitive Poetics: An Introduction (2020). First, the authors discuss critical comments put forward by scholars with respect to Stockwell’s earlier studies in cognitive poetics, and next, from a literary-studies perspective they carry out an overall assessment of the revisions and modifications introduced in the book’s current edition. Irrespective of some critical remarks, there is no doubt that thanks to the changes, the inspirational value of Stockwell’s book has been enhanced.